Efektivitas Media Pembelajaran Interaktif Berbasis Permainan Kahoot untuk Meningkatkan Evaluasi Hasil Belajar: The Effectiveness of Kahoot Game-Based Interactive Learning Media in Improving Learning Outcome Evaluation - Duti Sari Putra; Kabul Praptiyono; Mujiyanto Mujiyanto (ITScience (Information Technology and Science), 2026)
This study aims to determine the effectiveness of implementing the game-based interactive learning medium Kahoot in Buddhist Religious Education lessons on the learning outcomes of 10th-grade students at SMK Cluwak, Pati Regency, and to assess its effectiveness in improving student learning outcomes. The study was motivated by low student learning outcomes—which remained below the Minimum Mastery Criteria (KKM)—and the suboptimal use of interactive learning media in the instructional process. A quantitative approach was employed using an experimental method and a pretest-posttest control group design. The research subjects were 10th-grade students at SMK N 1 Cluwak, Pati Regency, specifically a single class comprising 15 Buddhist students. Data were collected through learning outcome tests administered before and after the intervention. The results indicate a significant improvement in student learning outcomes following the use of Kahoot; the class average score rose markedly from 57 in the pretest to 80 in the posttest. Inferential statistical analysis using the t-test further corroborated these findings, yielding a Sig. (2-tailed) value of 0.02 (< 0.05), which demonstrates the significant positive effectiveness of the intervention applied to the students. Kahoot’s gamification features and real-time quizzes effectively stimulated student cognitive engagement. The implementation of the interactive medium Kahoot proved significantly effective in enhancing the Buddhist Religious Education learning outcomes of 10th-grade students at SMK N 1 Cluwak, Pati Regency. This medium offers an innovative strategic alternative for boosting student engagement, motivation, and academic achievement.